ADAPTIVE ACCOUNTS RECEIVABLE MANAGEMENT FOR BAD DEBT MITIGATION DURING THE FOOT-AND-MOUTH DISEASE OUTBREAK: EVIDENCE FROM AN INDONESIAN DAIRY ENTERPRISE - Risky Nurfadila (Jurnal Ilmiah Mahasiswa Akuntansi Universitas Tulungagung, 2024)
The sustainability of agribusiness enterprises depends heavily on effective accounts receivable management, particularly when external crises disrupt debtors' repayment capacity. Despite extensive research on bad debts in commercial sectors, limited attention has been given to receivables management in the dairy industry during periods of biological and economic disruption. This study aims to identify the factors contributing to uncollectible accounts receivable and examine the receivables management practices implemented by CV. Pandowo Agung Milk, an Indonesian dairy enterprise. A qualitative descriptive case study approach was employed. Primary data were collected through semi-structured interviews and field observations involving company management and dairy farmers, while secondary data were obtained from company documents and receivables records. Data were analyzed using qualitative techniques consisting of data reduction, data presentation, and conclusion drawing. The findings reveal that the sharp increase in uncollectible accounts receivable in 2022 was primarily caused by external factors, particularly the Foot-and-Mouth Disease outbreak, which substantially reduced dairy farmers' milk production and weakened their repayment capacity. Rather than adopting aggressive debt collection practices, the company implemented adaptive receivables management strategies, including veterinary assistance, subsidies for medicines and disinfectants, repayment grace periods, and debt restructuring until livestock productivity recovered. These strategies helped preserve long-term relationships with farmers while maintaining business continuity. The study contributes to the literature by demonstrating that adaptive receivables management serves as an effective credit risk mitigation strategy during external crises. Practically, the findings provide insights for agribusiness enterprises in developing resilient credit management policies capable of sustaining financial performance under conditions of uncertainty.